A garantia da paz perpétua: considerações acerca do progresso histórico no Kant tardio - Queiroz, Pedro Allan Portácio de (2020)
This research aims to analyze a supposed semantic review of what Kant understood, in the nineties, as "guarantee of perpetual peace". such a review would be, according to this hypothesis, would be visible in the latest texts on the philosophy of history. In effect, for the philosopher, it is nature that drives that progresses the political-political process through the selfish tendencies of men, peoples and states. This conceptual and heuristic resource of a wise nature already appeared in 1784, in the work Idea for a Universal History with a Cosmopolitan Purpose and reappears in 1795, in the work Perpetual Peace. However, in 1798, in the second section of the work The Conflict of the Faculties, it is here that historical progress is possible because there is a moral disposition present in humanity, whose French Revolution (1789), served as a historical sign. We can show here at least two ways of executing progress: in the first moment, a history is seen as a hidden plane of the nature, which in turn uses man to make its fins, while in the second moment it is man himself who appears on the historical scene as the self-producer of its destiny. To explore the subtleties of this semantic review we split that research into three stages: apply, focus our attention on the exposition of the legal philosophy that underlies or the political project of perpetual peace; in a second moment, it presents these concepts for the scope of international relations, in order to situate ourselves properly in the political and historical challenge of peace; and finally, in the third moment, we proceed to the analysis of the texts that show the progress of the human race, in order to detect possible modulations in this concept, brings comments in favor and against an possible change in the Kantian argument. Our intention is to show that there are adequate textual elements to confirm that Kant, in fact, proceeds with a semantic reformulation of the problem of progress, as it is explicitly explained, in the last instance, in a moral disposition of the humanity to the right. However, we believe that, there is still no late Kant, a teleological perspective is not ruled out, being radicalized only in the most original horizon: man as the subject of history.